2022
DOI: 10.1109/jphotov.2021.3116017
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Lifetime Limitation of Industrial Ga-Doped Cz-Grown Silicon After Different Solar Cell Process Flows

Abstract: Gallium-doped silicon material has been rapidly gaining importance in the photovoltaic industry as a boron-oxygen defect-free material with promising minority carrier lifetime. We investigate the influence of different cell process flows [passivated emitter and rear cell tunneling-oxide-passivating contact, and a "hot oxidation" process] on the bulk material quality of an industrial Ga-doped Cz-grown silicon material, as well as its lightand elevated temperature induced degradation degradation behavior under l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…This is particularly important as the industry rapidly shifts from boron to gallium as the main dopant agent for p-type silicon. It is of great importance to identify the defect(s) responsible for lifetime instabilities recently observed in solar cells fabricated with p-type Ga-doped c-Si wafers, [119][120][121][122] as these wafers have the potential to enable a next-generation of high-efficiency silicon solar cells based on p-type c-Si wafers.…”
Section: Final Thoughtsmentioning
confidence: 99%
“…This is particularly important as the industry rapidly shifts from boron to gallium as the main dopant agent for p-type silicon. It is of great importance to identify the defect(s) responsible for lifetime instabilities recently observed in solar cells fabricated with p-type Ga-doped c-Si wafers, [119][120][121][122] as these wafers have the potential to enable a next-generation of high-efficiency silicon solar cells based on p-type c-Si wafers.…”
Section: Final Thoughtsmentioning
confidence: 99%
“…However, silicon wafers used in mass production generally have lower carrier lifetimes than those reported in refs. [18, 19] and the bulk Fe concentrations are likely higher. Moreover, additional contamination likely occurs during cell processing, which is difficult to quantify or generalize.…”
Section: Resultsmentioning
confidence: 99%
“…Some have reported a low bulk Fe concentration on the order of 10 9 cm −3 in state-of-the-art high-quality gallium doped Cz-Si wafers. [18,19] According to the simulation in Figure 6B, these high-quality wafers may not necessarily need very effective gettering to achieve 25% cell efficiency. However, silicon wafers used in mass production generally have lower carrier lifetimes than those reported in refs.…”
Section: Impact Of the Oxide Blocking Effects In A Typical Poly-si/si...mentioning
confidence: 99%
See 1 more Smart Citation
“…The silicon photovoltaic (PV) industry has recently moved away from boron (B) and transitioned to gallium (Ga) as the main dopant element for p-type Czochralski-grown silicon (Cz-Si) wafers, primarily to avoid the well-known boron-oxygen defect. [1,2] Although several articles have reported higher effective minority carrier lifetimes in Ga-doped wafers than in B-doped wafers, [3][4][5][6][7] detailed studies of the material quality of industrial Ga-doped ingots are still rather limited. Recently, Horzel et al [7] reported effective lifetimes in the range of 3-17 ms along a customgrown Ga-doped Cz ingot with a resistivity range of 5-12 Ω cm.…”
Section: Introductionmentioning
confidence: 99%